Pengaruh Pendidikan Agama Islam Terhadap Sikap Anak Single Parent - Su’udin Aziz; Farida Isroani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Islamic education in general can be understood as an effort to increase students' faith, understanding, appreciation and practice of the religion of Islam so that they become Muslim individuals who believe and are pious and have noble character in personal, social, national and state life. This study aims to reveal the effect of Islamic Religious Education on the Attitudes of Single Parent Children: 1) Implementation of Islamic Religious Education. 2) Attitude of Single Parent Children. 3) The Effect of Islamic Religious Education on the Attitude of Single Parent Family Children This research is a field research with quantitative approach with correlation method. The data collection techniques used are: 1) Observation Method 2) interviews (interviews) 3) questionnaires (questionnaires) 4) documentation. Data analysis techniques include calculating the average value (mean), product moment correlation techniques, and drawing conclusions. Based on the research that has been done, it can be concluded that Islamic religious education has a good influence on the attitude of single parent children.